Fungal volatile organic compounds: mechanisms involved in their sensing and dynamic communication with plants - Razo-Belmán, Rosario; Ángeles-López, Yesenia Ithaí; García-Ortega, Luis Fernando; León-Ramírez, Claudia Geraldine; Ortiz-Castellanos, Lucila; Yu, Houlin; Martínez-Soto, Domingo (Frontiers in Plant Science, 2023)
Microbial volatile organic compounds (MVOCs) are mixtures of gas-phase hydrophobic carbon-based molecules produced by microorganisms such as bacteria and fungi. They can act as airborne signals sensed by plants being crucial players in triggering signaling cascades influencing their secondary metabolism, development, and growth. The role of fungal volatile organic compounds (FVOCs) from beneficial or detrimental species to influence the physiology and priming effect of plants has been well studied. However, the plants mechanisms to discern between FVOCs from friend or foe remains significantly understudied. Under this outlook, we present an overview of the VOCs produced by plant-associate fungal species, with a particular focus on the challenges faced in VOCs research: i) understanding how plants could perceive FVOCs, ii) investigating the differential responses of plants to VOCs from beneficial or detrimental fungal strains, and finally, iii) exploring practical aspects related to the collection of VOCs and their eco-friendly application in agriculture.